Cardiac postacute sequelae symptoms of SARS-CoV-2 in community-dwelling adults: cross-sectional study. Issue 2 (5th September 2022) - Ogungbe, Oluwabunmi; Gilotra, Nisha A; Davidson, Patricia M; Farley, Jason E; Dennison Himmelfarb, Cheryl R; Post, Wendy S; Commodore-Mensah, Yvonne
Abstract : Objective: To examine risk factors for cardiac-related postacute sequelae of SARS-CoV-2 infection (PASC) in community-dwelling adults after acute COVID-19 infection. Methods: We performed a cross-sectional analysis among adults who tested positive for COVID-19. Outcomes were self-reported cardiac-related PASC. We conducted stepwise multivariable logistic regression to assess association between the risk factors (existing cardiovascular disease (CVD), pre-existing conditions, days since positive test, COVID-19 hospitalisation, age, sex, education, income) and cardiac-related PASC. Results: In a sample of 442 persons, mean (SD) age was 45.4 (16.2) years, 71% were women, 13% were black, 46% had pre-existing conditions, 23% had cardiovascular (CV) risk factors and 4% had CVD. Prevalence of cardiac PASC was 43% and newly diagnosed cardiac conditions were 27%. The odds for cardiac-related PASC were higher among persons with underlying pre-existing conditions (adjusted OR (aOR): 2.00, 95% CI: 1.28 to 3.10) and among those who were hospitalised (aOR: 3.03, 95% CI: 1.58 to 5.83). Conclusions: More than a third of persons with COVID-19 reported cardiac-related PASC symptoms. Underlying CVD, pre-existing diseases, age and COVID-19 hospitalisation are possible risk factors for cardiac-related PASC symptoms. COVID-19 may exacerbate CV risk factors and increase risk of complications.